Assessing patient-centered care in patients with chronic health conditions attending chiropractic practice: protocol for a mixed-methods study. Issue 1 (December 2016) - Stuber, Kent; Langweiler, Mark; Mior, Silvano; McCarthy, Peter
Abstract Background The management of chronic health conditions increasingly requires an organized, coordinated, and patient-centered approach to care. The Chronic Care Model (CCM) has been adopted in primary care to improve care delivery for those with chronic health conditions. Chiropractors manage chronic health conditions; however, little is known if such care is patient-centered. The primary aim of this study is to determine to what extent chiropractic patients with chronic health conditions perceive their care is patient-centred. We will assess concordance with the CCM using the Patient Assessment of Chronic Illness Care (PACIC) survey in study patients. We will also explore perception of how patient-centered the care provided by chiropractors is for those with chronic health conditions according to patients and chiropractors. Methods/design We will use a sequential mixed methods design with quantitative priority. In the quantitative component patients will complete a written questionnaire providing sociodemographic, health status, and health care interaction information, all of which will serve as the independent variables. Patients will also complete a modified version of the PACIC; the average overall score will be the dependent variable. In the qualitative component semi-structured interviews and focus groups with patients and chiropractors will be conducted. A pilot study will be conducted to determine if the modified PACIC will perform adequately in measuring concordance with the CCM for chiropractic care. Pilot testing will also allow for assessment of the interview and focus groups guides. Variables found to be significantly associated will be included in a multivariate linear regression analysis to identify significant predictors of the dependent variable. Qualitative data will be analyzed using an inductive thematic analysis to provide meaning to the quantitative results. Discussion There is a paucity of research describing the extent to which chiropractic care for patients with chronic health conditions is concordant with the CCM. This study will examine this relationship and the perceptions and experiences of patients and chiropractors regarding how patient-centered chiropractic care is for these patients.